Misdiagnosis of Ruptured Abdominal Aortic Aneurysm: Systematic Review and Meta-Analysis. (August 2014) - Azhar, Bilal; Patel, Shaneel R.; Holt, Peter J.E.; Hinchliffe, Robert J.; Thompson, Matt M.; Karthikesalingam, Alan
Purpose: To quantitatively summarize the incidence of misdiagnosis of ruptured abdominal aortic aneurysms (rAAA), the most common presenting features, and the commonest incorrect differential diagnoses. Methods: A systematic search according to PRISMA guidelines was performed using EMBASE and MEDLINE databases to identify studies reporting the initial rate of misdiagnosis of patients with rAAA. Random-effects meta-analyses were performed to estimate the rate of misdiagnosis, presenting features, and commonest differential diagnoses. A sensitivity analysis was performed for studies reporting after 1990. Results: Nine studies comprising 1109 patients contributed to the pooled analysis, which found a 42% incidence of rAAA misdiagnosis (95% CI 29% to 55%). In studies reporting after 1990, misdiagnosis was seen in 32% (95% CI 16% to 49%). The most common erroneous differential diagnoses were ureteric colic and myocardial infarction. Abdominal pain, shock, and a pulsatile mass were presenting features in 61% (49%–72%), 46% (32%–61%), and 45% (29%–62%) of rAAAs, respectively. Conclusion: The rate of misdiagnosis of rAAA has remained consistent over time and is concerning. There is a need for an effective clinical decision tool to enable accurate diagnosis and triage at the scene of the emergency.